ILUSI KEBENARAN DALAM PERSPEKTIF SHANKARA - Ilham Maulana (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
Recent times, news spreads fast without knowing whether the news is true or not. The truth was fought over. Each person/group claims that he or she is the truth while the others are wrong. Seeing this phenomenon, it seems to be interesting to see the illusionary concept of truth initiated by Shankara. For this reason, this article then discusses the illusionary concept (maya) of Adi Shankara (788-820), a mystic known as the Advaita Vedanta philosophy. It was Shankara who challenged what we had thought to be the truth. In the Advaita Vedanta it is taught that the only truth is Brahman. Apart from Brahman, everything is an illusion. The illusion of truth here—which is always conditioned—does not want to say that truth is relative, that is, there is no absolute truth because each person/group has their own version of truth. But that truth is transcendent, it is unreachable.